Metabolic adaptation of colonic microbiota to galactooligosaccharides: a proof‐of‐concept‐study. Issue 5 (12th January 2017) - Mego, M.; Manichanh, C.; Accarino, A.; Campos, D.; Pozuelo, M.; Varela, E.; Vulevic, J.; Tzortzis, G.; Gibson, G.; Guarner, F.; Azpiroz, F.
Summary: Background: Prebiotics have been shown to reduce abdominal symptoms in patients with functional gut disorders, despite that they are fermented by colonic bacteria and may induce gas‐related symptoms. Aim: To investigate changes in the metabolic activity of gut microbiota induced by a recognised prebiotic. Methods: Healthy subjects ( n = 20) were given a prebiotic (2.8 g/day HOST‐G904, HOST Therabiomics, Jersey, Channel Islands) for 3 weeks. During 3‐day periods immediately before, at the beginning and at the end of the administration subjects were put on a standard diet (low fibre diet supplemented with one portion of high fibre foods) and the following outcomes were measured: (i) number of daytime gas evacuations for 2 days by means of an event marker; (ii) volume of gas evacuated via a rectal tube during 4 h after a test meal; and (iii) microbiota composition by faecal Illumina MiSeq sequencing. Results: At the beginning of administration, HOST‐G904 significantly increased the number of daily anal gas evacuations (18 ± 2 vs. 12 ± 1 pre‐administration; P < 0.001) and the volume of gas evacuated after the test meal (236 ± 23 mL vs. 160 ± 17 mL pre‐administration; P = 0.006). However, after 3 weeks of administration, these effects diminished (11 ± 2 daily evacuations, 169 ± 23 mL gas evacuation). At day 21, relative abundance of butyrate producers (Lachnospiraceae) correlated inversely with the volume of gas evacuated ( r = −0.52; P = 0.02). Conclusion: The availability of substrates induces an adaptation of the colonic microbiota activity in bacterial metabolism, which produces less gas and associated issues. Clinical trials.gov NCT02618239. Abstract : Linked Content This article is linked to Staudacher paper. To view this article visithttps://doi.org/10.1111/apt.13976 .